The crosstalk between microbiome and mitochondrial homeostasis in neurodegeneration - Fivos Borbolis; Mytilinaiou, Eirini; Palikaras, Konstantinos (Cells, 2023)
Mitochondria are highly dynamic organelles that serve as the primary cellular energy-generating system. Apart from ATP production, they are essential for many biological processes, including calcium homeostasis, lipid biogenesis, ROS regulation and programmed cell death, which collectively render them invaluable for neuronal integrity and function. Emerging evidence indicates that mitochondrial dysfunction and altered mitochondrial dynamics are crucial hallmarks of a wide variety of neurodevelopmental and neurodegenerative conditions. At the same time, the gut microbiome has been implicated in the pathogenesis of several neurodegenerative disorders due to the bidirectional communication between the gut and the central nervous system, known as the gut-brain axis. Here we summarize new insights into the complex interplay between mitochondria, gut microbiota and neurodegeneration, and we refer to animal models that could elucidate the underlying mechanisms, as well as novel interventions to tackle age-related neurodegenerative conditions, based on this intricate network.
Keywords: Ageing; Alzheimer’s disease; Amyotrophic Lateral Sclerosis; gut-brain axis; Huntington’s disease; microbiome; Mitochondria; Neurodegeneration